#TITLE_ALTERNATIVE# - ILHAM NOOR (NIM. 151 08 016); Dr.techn. Dudy D. Wijaya, S.T., M.Sc.; Dr. Ir. Wedyanto Kuntjoro, AKBAR
Time series of any geodetic coordinate may consist of both tectonic and non-tectonic signals. An example of non-tectonic signal is Atmospheric Pressure Loading (APL). Global variations in surface pressure can displace the Earth’s surface by more than 1 cm in radial (vertical) and horizontal directions. Observational data from space geodesy are often used for geodynamic studies that seek a level of accuracy of position displacement in mm. Therefore, it is important to remove the displacement signals due to APL, which otherwise propagate into other parameters. In order to remove this effect, equations of geophysical approach and investigations on spatio-temporal characteristics of APL correction are required. Geophysical approach uses convolution of the actual loading distribution over the entire surface of the solid Earth. The required data input for this approach are surface pressure, reference pressure, position of observational station, land-sea mask, load love numbers (LLNs), and the Green’s function values. Based on the calculation of APL for 60 sample points over Sumatera and Java islands, it is found that APL effect can displace the Earth’s surface in the range of -2,8 mm to 4.1 mm for vertical direction and -1.9 mm to 3.1 mm for the horizontal one. According to spatio-temporal analysis of APL time series, it is found that the APL correction consists of diurnal, annual, as well as seasonal variations. Moreover, the magnitude of APL corrections depend on geographical latitude and proximity to the oceans.